HYPNOBIRTHING AS A NON-PHARMACOLOGICAL INTERVENTION TO REDUCE LABOR PAIN AND ANXIETY: A QUASI-EXPERIMENTAL STUDY - Alfadefi Khalifatunnisak; Anna Septina Andarini (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2026)
Labor pain and anxiety are major challenges faced by women during childbirth. High levels of stress can disrupt labor progress and lead to increased medical interventions. Hypnobirthing, a technique that utilizes breathing, visualization, and self-hypnosis, has emerged as a holistic and non-pharmacological approach to support laboring women. Objective: To evaluate the effectiveness of hypnobirthing in reducing labor pain intensity and maternal anxiety during the first stage of labor. This quasi-experimental study included 60 primigravida women at a maternity hospital. Participants were divided into an intervention group (hypnobirthing) and a control group (routine care). The intervention group received guided hypnobirthing sessions during the active phase of labor. Pain was measured using the Visual Analogue Scale (VAS), and anxiety was assessed using the Hamilton Anxiety Rating Scale (HAM-A). Data were analyzed using paired and independent t-tests. Women in the hypnobirthing group experienced a significant reduction in both anxiety and pain scores compared to the control group (p < 0.01). Hypnobirthing techniques contributed to a more positive and controlled labor experience.  Hypnobirthing is an effective non-pharmacological method to reduce labor pain and anxiety. It may be recommended as part of comprehensive antenatal education and labor management.